Contribution of the Classic Ideas on Social Class and its Impact on Mobility Studies - Rodríguez Holguín, Elizabeth; Ávila Martínez, Alexander (Revista de Filosofía, 2022)
Social inequality is no longer legitimized by natural or divine laws, and has become a central concern in different areas of knowledge. It has become study focus especially in the world of social sciences, where different theories, approaches and methodologies have been used to address the issue with a common axis: "social differentiation" as a starting point. It is understood as the conditions valued in a society for distribution and acquisition of tangible or intangible assets, leading to talk about social stratification. This article endeavors to make an approach to the study of social stratification from the viewpoint of the so called classical thinkers, delving into their contributions and importance in this field of research.